Utilization of Coffee Grounds as Coffee Shop Waste in Making Natural Body Scrubs - Trisyiah, Trisyiah; Amanda, Reskita; Azzahra, Nurul Fatimah; Nurhajawarsi, Nurhajawarsi; Thahir, Muhammad Taufiq (Jurnal Sains dan Teknik Terapan, 2025)
Coffee grounds are residues from brewing coffee powder with hot water, and their utilization remains limited. This study aims to develop a cream scrub based on coffee grounds with additional chemical ingredients such as stearic acid, cetyl alcohol, olive oil, TEA, glycerin, phenoxyethanol, vanilla fragrance, and propylene glycol. Two formulations were developed with different concentrations of coffee grounds: 2.4% (F1) and 3.9% (F2). The tests included pH analysis, water content, spreadability, homogeneity, Total Plate Count (TPC) testing, and organoleptic evaluation. The results showed that the cream scrub had a pH of 6, with water content of 52.3% for F1 and 46.5% for F2, and a spreadability of 5 cm. Both formulations were homogeneous without phase separation. Moisturizing tests scored 4 (good), with F1 achieving 53.3% and F2 46.7%. The aroma of F1 scored 4 (good) at 66.7%, slightly higher than F2 (63.3%). In terms of texture, F1 obtained 66.7% at a score of 4 (good), while F2 reached 56.7%. The color parameter of both formulations was similar, with a score of 5 (very good) at 26.7%. Irritation tests showed negative results for 93% of participants for F1 and 96% for F2.